Water-absorbing bags for high-altitude aerial firefighting: Mathematical modeling and drop pattern analysis - Haoran Sun; Chengyun Wu; Dachuan Zhang; Yang Wu; Renyu Hu; Yanmeng Wang; Yaru Tian; Chuyun Luo; Haitao Hu (Results in Engineering)
Firefighting aircraft are highly effective against forest fires, but hazardous low-altitude operations often lead to accidents. Increasing the flight altitude is an effective way to enhance flight safety; however, a higher dropping altitude can result in greater atomization of the liquid retardant, thereby reducing the thickness of the ground coverage. The use of firefighting bags can effectively prevent atomization, providing a viable solution to improve firefighting efficiency at higher drop altitudes. To analyze the effectiveness of firefighting bags, this paper establishes a mathematical model capable of calculating the bag falling trajectory and drop pattern characteristics. A kinetic model is built to solve the transient position and rotational attitude, and a ground pattern model is presented to obtain the coverage levels. The model is validated by a real-scale dropping experiment. The prediction deviations for the pattern lengths are 20 %, 16.1 %, and 18.75 %, respectively, while the prediction deviations for the 95 % pattern widths are -0.2 m, 0.1 m, and -0.8 m, respectively. The firefighting efficiency of the bags is further investigated under various conditions, and the results show that the effectiveness of the bags is not significantly affected by drop height and can achieve acceptable drop patterns in high-altitude dropping systems.